639 Emergency Surgical Approach to A Bleeding Pseudoaneurysm Of the Posterior Inferior Pancreaticoduodenal Artery After Failed Embolisation. (12th October 2021) - Manku, B; Gupta, N; Ahmad, J; McLaughlin, E
Abstract: Background: Pseudoaneurysms of visceral arteries are uncommon, with a prevalence of 0.01% to 0.2% 1 . Initial treatment is radiological embolisation (RE) 2 . If this fails, surgical access to the pseudoaneurysm is extremely difficult. They are associated with major complications such as rupture, ischaemia and shock 2, with a 20-70% mortality rate 3 . We report the case of a patient admitted with a life-threatening bleed from an aberrant inferior pancreaticoduodenal artery (IPDA) with failed RE. Case Summary: A 44-year-old patient presented with right upper quadrant pain, shock and low haemoglobin. His computerised tomography (CT) scan showed a large retroperitoneal haematoma with active bleeding from a 5x6mm IPDA pseudoaneurysm. After resuscitation, access to the IPDA during RE via the coeliac axis and superior mesenteric artery was unsuccessful and he deteriorated. He underwent an emergency laparotomy, which showed the retro-peritoneal haematoma had ruptured into the peritoneal cavity through the transverse mesocolon. Four-quadrant abdominal packing and supra-coeliac manual compression of the aorta was utilised. The right colon was mobilised with full kocherisation of the duodenum. The gastrocolic omentum was divided to enter the lesser sac. The haematoma was evacuated and bleeding branches from the IPDA were suture ligated. He required 26 units of blood throughout admission and underwent 24-hour damage control laparostomy on intensive care. CT mesenteric angiogram post-surgery and re-look laparotomy showed no further active bleeds. He had an uneventful recovery and discharged safely. Conclusions: RE of visceral artery pseudoaneurysms is challenging. Surgery remains the last resort and should be performed by appropriately trained specialist surgeons.